From Subversion to Celebration: The Emergence of a domestic avant garde in contemporary Irish Art - HUMPHRIES, JANE (My University, 2008)
Although the domestic has been critically observed in relation to British artists in the 1990s, it has not been considered cross-culturally in terms of Irish artists.1 Considering many female Irish artists were coming of age in the 1990s, as part of a newly enlightened media-aware generation, conscious of feminist ideas and changing attitudes towards women both in Ireland and internationally, this paper argues that consequently, the domestic, as a subject-matter or material culture, became the vanguard for a `domestic? artistic movement to develop.
PUBLISHED
Keywords: History of Art